Assertiveness Training Therapy to Adolescence Development - Meinrat Zhukov (International Journal of Science and Society, 2020)
During adolescent age, the teenagers are struggling for their self identity. The obstacle of teenagers to gain their self identity to some extent can be manifested through their deviant behaviors. The purpose of this scientific paper was to explore the result of Assertiveness Training to improve adolescence growth and development. Teenagers with a difficulty of being assertive were given Assertiveness Training. This was a quasi-experimental research, using pre-post without control group. A number of 16 samples were recruited using purposive sampling technique. The results of these interventions showed the improvement particularl on diferrent aspects and developmental task of teenagers, especially in emotion and psychosocial aspecs. Assertiveness Training was recommended that this report would be utilized as a standard of mental health-psychiatric nursing specialized treatment and to be socialized at all community mental health care settings.